BAPPEDA Role Analysis in Regional Development Planning - Fitriani; Rabina Yunus; Andi Muhammad Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
Badan Perencanaan Pembangunan Daerah (Bappeda) is a body that has an important task in regional development planning. Bappeda assists the Regional Head in determining policies in the field of regional development planning and assessing their implementation. This research aims to find out the role of the Regional Development Planning Agency in the development planning process in the Pasangkayu Regency area and also to find out the policy formulation process. This research uses a qualitative approach with a case study method, which is a method used to elaborate on and understand the meaning ascribed to social or humanitarian problems. The result of this research is that the Regional Development Planning Agency has an important role in carrying out the function of coordinating regional development planning with all agencies in the government in order to realize a new planning system that must be comprehensive. Factors supporting policy formulation include coordination, community participation, and government commitment. Meanwhile, the factors that hinder the policy formulation process include budget adjustment and readiness, too many proposals, and limited supporting documents.